Influence of maternal diet during lactation and use of formula feeds on development of atopic eczema in high risk infants. Issue 6693 (22nd July 1989) - Chandra, R. K.; Puri, S.; Hamed, A.
Abstract : OBJECTIVE–To examine the effects of maternal diet during lactation and the use of formula feeds on the development of atopic eczema in infants at risk. DESIGN–Mothers who planned to breast feed exclusively were randomly allocated to either a restricted diet (avoiding milk and other dairy products, eggs, fish, peanuts, and soybeans) or a diet without restrictions. Mothers who did not plan to breast feed were randomly allocated to using one of three formula feeds. SETTING–Child health centre in Canada. SUBJECTS–97 Mothers who chose to breast feed and 124 mothers who did not. INTERVENTIONS–Restricted diet for 49 mothers who breast fed. Casein hydrolysate formula, soy milk formula, or cows' milk formula for infants not breast fed. MAIN OUTCOME MEASURE–Development of eczema in babies. RESULTS–Infants were followed up over 18 months and examined for eczema. Eczema was less common and milder in babies who were breast fed and whose mothers were on a restricted diet (11/49 (22%) v 21/48 (48%)). In infants fed casein hydrolysate, soy milk, or cows' milk 9/43 (21%), 26/41 (63%), and 28/40 (70%), respectively, developed atopic eczema. CONCLUSIONS–In families with a history of atopic disease [corrected] mothers who breast feed should avoid common allergenic foods during lactation. If they choose not to breast feed a hydrolysate formula should be used.